Preparation of Activated Carbon/N-doped Titania Composite for Synergistic Adsorption-photocatalytic Oxidation of Batik Dye - Azrina, Abd Aziz; Shaliza, Ibrahim (IOP Publishing, 2018)
A synergetic improved composite TiO2 photocatalysts was successfully synthesized by using nitrogen (N) as a dopant and activated carbon (AC) as synergetic compound. Two different types of AC prepared from Garcinia mangostana shell and commercial AC obtained from palm shell were chosen as synergetic compound. Thus synthesized composites was further characterized by Brunauer-Emmett-Teller (BET) surface analyzer and UV-visible light spectroscope. The doping of N resulted in a better solar light utilization potential. Furthermore, synergizing with AC contributed for the improved BET surface area and pore size distribution. The synergetic adsorption-photocatalytic activity was investigated by removing a commercial batik dye namely Remazol Brilliant Blue (RBB) under direct solar irradiation. The synergetic experiments showed that commercial AC synergized with N-TiO2 resulted with a maximum removal efficiency of ~80% in 6 h.